Far-Right Local Governments and Civil Society: Findings from France and Italy - Seongcheol Kim (Political Studies Review, 2022)
The rise of far-right parties across Europe and their entrance into government at the local, if not regional or national, levels pose challenges for established civil society actors. This article draws on early findings from an ongoing research project in order to present two case studies of far-right local governments in small industrial towns in France and Italy: Hayange and Sant'Agata Bolognese. Keying in on these local administrations' approaches to civil society and drawing on semi-structured interviews with local politicians and trade union actors, the article identifies preliminary patterns in far-right local government relations with civil society organizations (including trade unions), including a bypassing or outright attacking of established associations deemed hostile (especially left-wing ones) in favor of those deemed politically more palatable. This exclusionary and partisan approach to civil society notably coexists alongside other aspects of far-right local governance centered on a performatively enacted claim to serve the entire community, most notably with the highly visible provision of non-excludable public goods such as public fountains and rotaries. These considerations provide a basis for ongoing and future work on far-right interventions in different areas of civil society, in different countries, and in light of a broader spectrum of actor perspectives.
Keywords: 300; civil society; far right; France; Italy; local government; trade unions